ADVANCES AND FUTURE DIRECTIONS IN HER2-POSITIVE BREAST CANCER: A NARRATIVE REVIEW - Agnieszka Pruska; Katarzyna Kleszczewska; Natalia Senatorska; Julia Rarok; Daria Godlewska; Hanna Pietruszewska; Monika Banaszek; Agata Panfil; Julia Błocka; Agata Lurka (International Journal of Innovative Technologies in Social Science, 2025)
HER2-positive breast cancer, characterized by the overexpression of the human epidermal growth factor receptor 2, accounts for 15-20% of all breast tumors and has historically been associated with a more aggressive phenotype. However, the prognosis for patients with HER2-positive metastatic breast cancer has dramatically improved in recent years due to significant therapeutic advancements. The development of HER2-directed therapies has revolutionized breast oncology, with trastuzumab marking a pivotal moment in 1998 with its FDA approval as the first-line adjuvant therapy (Chilà et al., 2021; Gampenrieder et al., 2020; Tarantino et al., 2021; Najjar et al., 2022). This narrative review summarizes the current and emerging therapeutic landscape for HER2-positive breast cancer, including novel anti-HER2 therapies such as monoclonal antibodies with enhanced properties, bispecific antibodies, and small molecules. This narrative review discusses the basic biology of HER2, its signaling pathways, and the mechanisms of action of available anti-HER2 modalities. A particular focus will be placed on the impact of novel antibody-drug conjugates (ADCs) and tyrosine kinase inhibitors (TKIs), which have shown remarkable efficiency, particularly in challenging scenarios like brain metastasis. These therapies, exemplified by trastuzumab deruxtecan and tucatinib, represent significant progress in overcoming resistance and improving patient outcomes. This review will also explore current and future trends in systemic therapy for HER2-positive metastatic breast cancer, aiming to highlight innovative strategies to overcome resistance and improve long-term patient outcomes (Gampenrieder et al., 2020; Mercogliano et al., 2023; Najjar et al., 2022; Rao et al., 2025; Guidi et al., 2023; Cano et al., 2023). Ultimately, it aims to provide clinicians and researchers with a concise, updated synthesis of emerging HER2-targeted strategies and their clinical implications.